User’s satisfaction on traveling facilities for senior citizen at Kuala Lumpur International Airport (KLIA) & Kuala Lumpur International Airport 2 (KLIA 2) / Muhammad Shahrin Safri - Safri, Muhammad Shahrin (2016)
An international airport depicts huge airport that has extensive area. From the design perspective, a huge airport is relevant due to the amount of airport users nowadays. Airport also has become country landmarks across the world. In other perspective shows the huge airport is complicating to user of the airport to walk along the airport if the traveling facilities is limited. The purpose of this research being conducted is to determine the satisfaction level on traveling facilities at the airports and to identify the type of traveling facilities provided at the airports. The selections of the senior citizen as the respondents due to the many of issues faced by them in term of traveling facilities at the airports. Besides, Kuala Lumpur International Airport (KLIA) and Kuala Lumpur International Airport 2 (KLIA2) as the case studies are precisely due to the airports are international airports. This study will carry out with mixed method of methodology which is quantitative and qualitative method. The satisfaction level for both airports was identified and the result shows the different for several aspects. Based the observation, there are several advantages and disadvantages of the traveling facilities provided. The result of this research shows that the needs of sufficient traveling facilities is crucial